Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2024)
We are delighted to present a diverse collection of articles that delve into the intricate relationship between law and technology across various regions and legal landscapes. This edition covers topics such as the development of the Indian telecommunication sector over the past decade, focusing on the merits and challenges of telecom and competition laws, as well as on 5G neutrality in the country. Other contributions address the rise of digital forensics in Kazakhstan’s cybercrime investigations and maritime cyber security. The issue also examines public policies on internet access and connectivity as a social right in Colombia’s Valle de Aburrá and assesses the effectiveness of Brazilian educational connectivity policies. One article analyzes the spread of false news and discriminatory content under Indonesia’s Information and Electronic Transactions Law, while another explores the risks of laundering criminal proceeds through cryptocurrency transactions. Additionally, there is a discussion on remote work in Portugal, focusing on work tools and expense reimbursement. Privacy concerns are explored through a comparative study of India, the USA, and South Africa, and another piece investigates internet access as a human right with socio-collective implications. The edition concludes with an article on measures to combat internet fraud in Kazakhstan and one piece on the legal and ethical challenges of regulating humanoid robots and artificial intelligence.